ANALYSIS OF ENVIRONMENTAL SANITATION CONDITIONS AND THE SPREAD OF INFECTIOUS DISEASES AFTER FLOOD DISASTER IN KUALA SIMPANG CITY - Pusvita, Dela (Akupun Tour Publisher, 2024)
Background: Flood disasters hit Indonesia almost every rainy season. Based on the value of losses and the frequency of flood disasters, there is a fairly high increase. The results of the preliminary survey showed that there were differences in disease patterns before and after the flood. Post-flood showed an increase in environmentally-based diseases. Likewise, changes occurred in the health conditions of the polluted environment. The purpose of this study was to analyze cases of infectious diseases and environmental sanitation conditions after the flood disaster in Kuala Simpang City. Purpose: The research was conducted in Kuala Simpang, Aceh Tamiang Regency, Aceh Province. Method: This type of research is descriptive qualitative as a type of research whose findings are not obtained through statistical procedures or other forms. The informants in this study numbered 4 people consisting of 1 Head of the Health Department Health Office and 3 staff from 3 health centers. Qualitative data analysis uses the stages of data reduction, data comparison and data used. Results : The results of the study showed that environmental sanitation conditions and disease spread patterns before and after the flood were very different, where before the flood the environmental sanitation conditions owned by the community were partly in good condition and diseases due to the environment rarely occurred, but after the flood all environmental sanitation in the community became bad and the spread of diseases due to the environment also increased. Disscusion and Conclusion: Local governments are expected to work with the Health Department and health workers to assist communities in building supporting facilities for the implementation of good sanitation to prevent disease in the community.